Answer:
x² + y² - 4x + 2y - 11 = 0
Explanation:
(x - h)² + (y - k)² = r²
h = the x-value of the center given
k = the y-value of the center given
r = radius
We know that;
h = 2
k = -1
r = 4
Now we can substitute in the values:
(x - 2)² + (y -(-1))² = 4²
(x - 2)² + (y + 1)² = 16
(x² - 4x + 4) + (y² + 2y + 1) = 16
=> x² - 4x + y² + 2y = 16 -4 - 1
=> x² - 4x + y² + 2y = 11
=> x² + y² - 4x + 2y = 11
=> x² + y² - 4x + 2y - 11 = 0 ⇒ Final Equation
I have attached the picture below of a circle of this equation, and it turns out exactly the same as the one shown in the question which tells us that the equation is correct!
Hope this helps!